RPE vs. Percentage 1RM Loading in Periodized Programs Matched for Sets and Repetitions - Helms, Eric R.; Byrnes, Ryan K.; Cooke, Daniel M.; Haischer, Michael H.; Carzoli, Joseph P.; Johnson, Trevor K.; Cross, Matthew R.; Cronin, John B.; Storey, Adam G.; Zourdos, Michael C. (Frontiers in Physiology, 2018)
Purpose: To investigate differences between rating of perceived exertion (RPE) and percentage one-repetition maximum (1RM) load assignment in resistance-trained males (19-35yrs) performing protocols with matched sets and repetitions differentiated by load-assignment. Methods: Participants performed squats then bench press 3x/wk in a daily undulating format over 8-weeks. Participants were counterbalanced by pre-test 1RM then assigned to percentage 1RM (1RMG, n = 11); load-assignment via percentage 1RMs, or RPE groups (RPEG, n = 10); participant-selected loads to reach target RPE ranges. Ultrasonography determined pre and post-test pectoralis (PMT), and vastus lateralis muscle thickness at 50 (VLMT50) and 70% (VLMT70) femur-length. Results: Bench press (1RMG +9.64 ± 5.36; RPEG +10.70 ± 3.30 kg), squat (1RMG +13.91 ± 5.89; RPEG +17.05 ± 5.44 kg) and their combined-total 1RMs (1RMG +23.55 ± 10.38; RPEG +27.75 ± 7.94 kg) increased (p < 0.05) in both groups as did PMT (1RMG +1.59 ± 1.33; RPEG +1.90 ± 1.91 mm), VLMT50 (1RMG +2.13 ± 1.95; RPEG +1.85 ± 1.97 mm) and VLMT70 (1RMG +2.40 ± 2.22; RPEG +2.31 ± 2.27 mm). Between-group differences were non-significant (p > 0.05). Magnitude-based inferences revealed 79, 57, and 72% chances of mean small effect size (ES) advantages for squat; ES 90% confidence limits (CL) = 0.50 ± 0.63, bench press; ES 90% CL = 0.28 ± 0.73, and combined-total; ES 90% CL = 0.48 ± 0.68 respectively, in RPEG. There were 4, 14 and 6% chances 1RMG had a strength advantage of the same magnitude, and 18, 29 and 22% chances, respectively of trivial differences between groups. Conclusions: Both loading-types are effective. However, RPE-based loading may provide a small 1RM strength advantage in a majority of individuals.